The Impact of Perceived Dysfunctional Parenting Styles on Level of Emotional Intelligence of Young Adults (Journal of Asian Development Studies, 2024)
The present study focused on youngadults'perception of theirparents'parenting styles, as they perceived them in the sixteen years of their lives, and their impact on their level of emotional intelligence. It was hypothesized that there would be a relationship between different parenting styles and the youngadults'emotional intelligence level. The study sample was randomly drawn from various University of Sindh and Jamshoro departments. The total sample was 120 participants (male 30, female = 90) with a mean age of (M= 21.7, SD = 1.7). Two questionnaires were used to collect the data for the study. Parker et al. (1997) developed measures of parenting style Scale (MOPS) and Emotional Intelligence Scale developed by Schutte et al. (1998). Data was analyzed with the help of IBM SPSS (version 28). Results indicated that overall dysfunctional parenting styles (mother and father) are unrelated to the youngadults'emotional intelligence level except for one subscale of the mother version, i.e., over control, which is significantly relatedto emotional intelligence. No significant gender difference was found on the parenting style scale (mother and father versions) or emotional intelligence scale. The results of the current study give valuable insight into cultural sophistication in understanding parenting styles and their impact on positive behaviors in youth. Findings can also be helpful for mental health professionals to understand risk factors contributing to themental health problems of young adults, develop interventions, and facilitate positive parenting practices.